Public interest influences in competition law : a comparative analysis of South Africa and Germany - Willing, Tim Maximilian (Department of Commercial Law, 2016)
The primary aim of this study is to identify the characteristics of the South African and German merger control regime with regard to public interest influences in order to compare the different approaches and conclude whether one system could learn anything from the other system and how it is implemented. In addition, it will investigate the casuistry on the legal terms and possible approaches to make a balancing of the competition and public interest effects more concrete. First, this paper will examine both merger regimes separately including a short introduction on the legislative background and an analysis of the merger cases before comparing the systems and coming to a conclusion. Emphasis is put on the investigation of the central public interest ground of employment. The casuistry in both countries falls short of more than some rules of thumb. Economic evaluations that become more detailed through the development of economic models should form the starting point for balancing deliberations, especially in Germany. Whereas the South African model promotes the evaluation of public interests intending to fight the inequalities of the past while also strengthening the economy, the German system gives preference to the independence of its Federal Cartel Office consequent to its focus on competition concerns allowing a ministerial authorisation only in exceptional circumstances. The paper will illustrate the advantages and disadvantages of both systems. The structural differences, in particular in terms of the competent decision making body, are justified on grounds of the different stages of development and the subsequently consistent goals aimed at in the respective country. The thesis therefore suggests that based on these circumstances, the systematic approaches which are tailored to the needs should not be changed. However, it is argued that the German Minister should exploit the full potential of § 42 ARC, especially through the use of appropriate remedies. Furthermore, it is recommended that South African competition authorities follow the objectives of the South African Competition Act with increased readiness and effort. The unique feature of the South African merger control with a mandatory public interest test which is included in the competition assessment has the potential to become a role model for other similarly situated countries with newly developing merger control systems in the future.